Prostitution, stigma and health: health promoting practices for sex professionals – an experience report (Research, Society and Development, 2022)
Experience report on the development of an operative group carried out in a brothel existing in a territory of a municipality in the interior of Ceará. The intervention aimed to provide spaces for health promotion for sex workers, boosting their access to Primary Health Care (PHC) actions and services, raising awareness of the importance of active participation in their health care process. The distance of this population from the health services is noticed, with this, the importance of the development of actions that will promote processes of reflection and autonomy of sex professionals with regard to prevention and health care, to the functioning of the services, as well as their rights and duties to health and citizenship, promoting an improvement in the assistance offered.